Endobronchial Manifestations of the Novel Coronavirus Infection (COVID-19): Data from the Endoscopy Unit of a COVID-19 Hospital - M. L. Shteiner; Yu. I. Biktagirov; A. V. Zhestkov; E. V. Makova (Журнал инфектологии, 2025)
Study objective. To identify features of endobronchial symptoms, includingincluding whether there is a relationship between the characteristics of endobronchial findings and the predominance of a particular COVID-19 viral strain during specific time intervals.Materials and methods. This study analyzed the results of 668 (100%) initial bronchoscopies performed in patients with COVID-19. All procedures were carried out in an endoscopy unit or intensive care setting. To assess the frequency of various events, the chi-square (χ2) test was used to evaluate the equality of proportions, with a significance level of p = 0.05.Results. Two distinct time periods were provisionally identified, differing in endobronchial symptomatology. During the first period, the predominant circulating strains of COVID-19 were Alpha, Beta, Gamma and Delta. The onset of the second period approximately coincided with the dominance of the Omicron variant. In the first time period (278 primary bronchoscopies, 41.617%), inflammatory changes of the bronchial mucosa were mild, and hemorrhagic endobronchial syndrome was frequently observed. There were 4 cases (0.599%) of endobronchial ulcers requiring morphological and bacteriological verification. A purulent component of endobronchial inflammation was rare (14 cases, 2.096%) and occurred only in the presence of pre-existing bronchial obstructive disease. In the second time period, purulent inflammation became widespread, while hemorrhagic endobronchial syndrome nearly completely resolved. In most cases, bronchial obstruction during this period was directly attributable to COVID-19. All observed differences were statistically significant.Conclusion. Endobronchial findings in patients with COVID-19 are nonspecific, lack pathognomonic features and generally align with the typical presentation of endobronchitis. Prior to the emergence of the Omicron variant, the endobronchial picture was characterized by mild inflammatory changes and hemorrhagic endobronchial syndrome. During the Omicron-dominant period, inflammatory changes intensified against the backdrop of an almost complete resolution of hemorrhagic endobronchial syndrome.